A rare presentation of shingles (herpes zoster) in an infant - Nair, P M C; James, Jemila; Soumya, S (Indian Journal of Child Health, 2016)
Herpes zoster (HZ) in children is very rare. We report a case of HZ in an infant which responded well to the treatment. HZ should also be considered in an infant with vesiculo-bullous lesion in a dermatomal distribution.